Comparison of Frailty Indicators Based on Clinical Phenotype and the Multiple Deficit Approach in Predicting Mortality and Physical Limitation - Woo, Jean; Leung, Jason; Morley, John E. (Journal of the American Geriatrics Society (JAGS), 2012)
Objectives To compare three simple bedside tools based on frailty phenotypes with a Frailty Index using the multiple deficit approach in the prediction of mortality and physical limitation after 4 years. Design Cohort study. Setting Hong Kong, China. Pariticipants Four thousand men and women aged 65 and older living in the community who were ambulatory enough to attend the study center. Methods Interviewers obtained information regarding physical, psychological, and functional health; body mass index (BMI), grip strength, blood pressure, and ankle brachial index were determined. Three clinical frailty scales based on the Fried phenotype (Cardiovascular Health Study (CHS); Fatigue, Resistance, Ambulation, Illness, and Loss (FRAIL); and Hubbard) and a frailty index (FI) were constructed from these variables, and their ability to predict incident mortality and physical function limitations was compared using receiver operating characteristic (ROC) curves. Results All tools predicted adverse outcomes. More participants were categorized into frail and prefrail categories using the CHS than with the other two clinical scales. For all frailty measures, with increasing levels of frailty, the sensitivity fell and the specificity increased to greater than 90%; the area under the ROC curve values were approximately 0.6. Conclusion Simple frailty scores are comparable with a multidimensional deficit accumulation FI in predicting mortality and physical limitations. The newer FRAIL, proposed for use in a clinical setting, is comparable with other existing short screening tools, as well as tools based on the multiple‐deficits model used for research settings. Addition of a physical performance measure to screening tools may increase predictive accuracy.